Detecting broken rotor bars with zero-setting protection - Pezzani, Carlos Martín (2014)
Broken rotor bars in induction motors can be dependably detected by analyzing the current signatures under sufficient motor load conditions. Detection becomes less dependable under light motor load conditions. There are also cases in which tolerable motor operating conditions generate current signatures similar to those of motors with broken rotor bars. These cases may present security concerns when the detection element is set to trip the motor and to send alarms. In this paper, we: Show how broken rotor bars cause characteristic current signatures. Show how to detect broken rotor bars with a zero-setting protection element, which uses the current signature method. Use cases with different motor operating and fault conditions to analyze the performance of the zero-setting broken bar protection element. Identify cases when the current signature method is dependable and cases when security is a concern. Present solutions to address security concerns.